Modified Antia-Buch Flap Incorporating an Extended Temporal Scalp Incision. Issue 2 (13th February 2023) - Maglic, Dino; Sudduth, Jack D.; Marquez, Jessica L.; Tieman, Joshua; Overschmidt, Bo; Siddiqi, Faizi; Gociman, Barbu
Abstract : Background: The Antia-Buch flap is a popular reconstructive method for full-thickness ear defects involving the helical rim. However, scaphal or conchal resection is often required to prevent ear distortion. Noel et al described a modified technique to the Antia-Buch flap, which includes an incision in the temporal scalp and complete detachment of the preauricular helical root to increase mobility of the flap. Since then, no studies have reported on the use of this modification. We report our experience in implementing Noel et al's modification of the Antia-Buch flap for helical rim defects. Methods: The modified technique differs from the original Antia-Buch flap by completely detaching the root of the helix and adding a vertical incision to the temporal scalp to increase mobility of the flap. No scaphal resection is necessary. After complete elevation of the flaps, the flaps are advanced and inset toward each other followed by closure. Results: In our practice, 10 patients have been treated with Noel et al's modification to the Antia-Buch flap. In each of these patients, acceptable reconstruction of the helical rim was able to be achieved. All the patients were pleased with their reconstructive outcome and ear anatomy was able to be successfully maintained. Conclusions: The modified Antia-Buch flap has shown to be an excellent method for large, helical rim defects, creating versatility by adding the temporal scalp incision. Our outcomes with Noel et al's modification to the original Antia-Buch flap support this method as a versatile technique for wide full-thickness helical rim defects.